Chemical Composition and Biological Activity of Mentha longifolia L. Essential Oil Growing in Taif, KSA Extracted by Hydrodistillation, Solvent Free Microwave and Microwave Hydrodistillation. Issue 1 (2nd January 2018) - Abdel-Hameed, El-Sayed S.; Salman, Mahmood S.; Fadl, Mohamed A.; Elkhateeb, Ahmed; Hassan, Mohamed M.
Abstract: Essential oils of aromatic plants as an important phytochemical class have been recognized for many years as a great source of pharmaceutical agents and food additives. There are many factors influencing the chemical composition of the essential oils including extraction techniques. In this project, the effect of extraction methods (hydrodistillation, microwave assisted hydrodistillation and solvent free microwave extraction) of Mentha longifolia L. growing in Taif, KSA on the yield and chemical composition of their essential oils were investigated. In addition, anticancer and antimicrobial activities of essential oils obtained were determined. The results showed no great difference between the oil yield obtained by the three different methods, but the methods used microwave were rapid, saving time and energy than the hydrodistillation method. The qualitative chemical compositions of the three oils for each species were similar with little quantitative differences of some compounds between the three methods. The oils consist mainly from monoterpenes and sesquiterpenes in which pulegone was the main component. All essential oils showed high antibacterial activity and moderate in vitro anticancer activity. In conclusion, this considered the first study represented the effect of microwave extraction in the chemical composition of M. longifolia essential oil growing in Taif, KSA. The authors recommended the usage of the microwave method in the extraction of mint essential oil because it is energy and time saving, in addition to environmentally friendly.